Randomised clinical trials: linaclotide phase 3 studies in IBS‐C – a prespecified further analysis based on European Medicines Agency‐specified endpoints. Issue 1 (1st November 2012) - Quigley, E. M. M.; Tack, J.; Chey, W. D.; Rao, S. S.; Fortea, J.; Falques, M.; Diaz, C.; Shiff, S. J.; Currie, M. G.; Johnston, J. M.
Summary: Background: Treatment options that improve overall symptoms of irritable bowel syndrome with constipation (IBS‐C) are lacking. Aim: A prespecified further analysis to evaluate the efficacy and safety of linaclotide, a guanylate cyclase C agonist, in patients with IBS‐C, based on efficacy parameters prespecified for European Medicines Agency (EMA) submission. Methods: Two randomised, double‐blind, multicentre Phase 3 trials investigated once‐daily linaclotide (290 μg) for 12 weeks (Trial 31) or 26 weeks (Trial 302) in patients with IBS‐C. Prespecified primary endpoints were the EMA‐recommended co‐primary endpoints: (i) 12‐week abdominal pain/discomfort responders [≥30% reduction in mean abdominal pain and/or discomfort score (11‐point scales), with neither worsening from baseline, for ≥6 weeks] and (ii) 12‐week IBS degree‐of‐relief responders (symptoms 'considerably' or 'completely' relieved for ≥6 weeks). Results: Overall, 803 (Trial 31) and 805 patients (Trial 302) were randomised. A significantly greater proportion of linaclotide‐treated vs. placebo‐treated patients were 12‐week abdominal pain/discomfort responders (Trial 31: 54.8% vs. 41.8%; Trial 302: 54.1% vs. 38.5%; P < 0.001) and IBS degree‐of‐relief responders (Trial 31: 37.0% vs. 18.5%; Trial 302: 39.4% vs. 16.6%; P < 0.0001). Similarly, significantly more linaclotide‐ vs. placebo‐treated patients were responders for ≥13 weeks in Trial 302 (abdominal pain/discomfort: 53.6% vs. 36.0%; IBS degree‐of‐relief: 37.2% vs. 16.9%; P < 0.0001). The proportion of sustained responders (co‐primary endpoint responders plus responders for ≥2 of the last 4 weeks of treatment) was also significantly greater with linaclotide vs. placebo in both trials ( P < 0.001). Conclusion: Linaclotide treatment significantly improved abdominal pain/discomfort and degree‐of‐relief of IBS‐C symptoms compared with placebo over 12 and 26 weeks. Trial registration: ClinicalTrials.gov (identifiers: NCT00948818 and NCT00938717).